2019
DOI: 10.3390/nu11061199
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3-DHA and Delta-Tocotrienol Modulate Lipid Droplet Biogenesis and Lipophagy in Breast Cancer Cells: the Impact in Cancer Aggressiveness

Abstract: Omega 3-docosahexaenoic acid (DHA) and vitamin E Delta-tocotrienol (Delta-T3) are extensively studied as protective nutrients against cancer development. Little is known about the biological mechanisms targeted by these bioactive molecules on lipid droplet (LD) biogenesis, an important breast cancer aggressiveness marker, and the occurrence of lipophagy in breast cancer cells. The aim of this study was to investigate the effect of DHA, Delta-T3 and DHA plus Delta-T3 co-treatment in LD biogenesis and lipophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 95 publications
2
15
0
1
Order By: Relevance
“…Additionally, Straka et al [55] and Maillard et al [56] observed increased accumulation of C20:5, c,c,c,c,c-∆5,8,11,14,17 and C22:6, c,c,c,c,c,c-∆4,7,10,13,16,19 in breast adipose tissue of women at high risk of breast cancer; the accumulation resulted from both diet supplementation and increased fish consumption. These results are in line with numerous studies demonstrating anticarcinogenic properties of long chain PUFA [36,57,58]. Novel preventive and therapeutic approaches include the attempts to use nanoparticle formulations for PUFA internalisation into cancer cells [59].…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, Straka et al [55] and Maillard et al [56] observed increased accumulation of C20:5, c,c,c,c,c-∆5,8,11,14,17 and C22:6, c,c,c,c,c,c-∆4,7,10,13,16,19 in breast adipose tissue of women at high risk of breast cancer; the accumulation resulted from both diet supplementation and increased fish consumption. These results are in line with numerous studies demonstrating anticarcinogenic properties of long chain PUFA [36,57,58]. Novel preventive and therapeutic approaches include the attempts to use nanoparticle formulations for PUFA internalisation into cancer cells [59].…”
Section: Discussionsupporting
confidence: 85%
“…There are other targets in lipid signalling pathways [329], and potential intervention may include modulation of lipid droplets biogenesis and lipophagy [330], but the research on the mechanisms involved in these pathways and their role in the genesis and progression of cancer is still ongoing. Thus, the development of substances that would effectively disrupt lipid metabolism in cancer cells without toxic effects in normal cells remains a great challenge for experimental oncologists.…”
Section: Targeting Lipid Metabolism In Cancer Treatmentmentioning
confidence: 99%
“…DHA enhances the anticancer drug oxaliplatin-induced autophagic cell death via activating Sestrin 2 and increasing ER stress in CRC cells [ 292 ]. Co-treatment with DHA and vitamin E delta-tocotrienol (Delta-T3) reduces lipid droplet biogenesis and potentiates lipophagy in TNBC MDA-MB-231 cells, resulting in the mitigation of breast cancer malignancy [ 293 ].…”
Section: Natural Products As Inducers Of Autophagy In Cancermentioning
confidence: 99%
“…DHA enhances the anticancer drug oxaliplatin-induced autophagic cell death via activating Sestrin 2 and increasing ER stress in CRC cells [292]. Co-treatment with DHA and vitamin E delta-tocotrienol (Delta-T3) reduces lipid droplet biogenesis and potentiates lipophagy in TNBC MDA-MB-231 cells, resulting in the mitigation of breast cancer malignancy [293] Several histone deacetylase inhibitors (HDACIs), such as trichostatin A (TSA), SAHA (also known as vorinostat) and depsipeptide, have been widely studied as cancer therapeutic agents. TSA-induced apoptosis is associated with multiple mechanisms, with the most likely being the modulation of autophagy.…”
Section: Omega-3 Polyunsaturated Fatty Acids (ω-3-pufa)mentioning
confidence: 99%